Brentuximab vedotin consolidation after autologous stem cell transplantation for Hodgkin lymphoma: A Fondazione Italiana Linfomi real‐life experience. Issue 1 (1st November 2021) - Massaro, Fulvio; Pavone, Vincenzo; Stefani, Piero Maria; Botto, Barbara; Pulsoni, Alessandro; Patti, Caterina; Cantonetti, Maria; Visentin, Andrea; Scalzulli, Potito Rosario; Rossi, Andrea; Galimberti, Sara; Cimminiello, Michele; et al.
Abstract: The standard management for relapsed or refractory classical Hodgkin lymphoma (cHL) is salvage therapy followed by autologous stem cell transplantation (ASCT). This strategy allows almost 50% of patients to be cured. Post‐ASCT maintenance treatment with brentuximab vedotin (BV) confers improved progression‐free survival (PFS) to cHL patients at high risk of relapse. We investigated the outcome of 105 cHL patients receiving post‐ASCT BV maintenance in the real‐life setting of 23 Italian hematology centers. This population included naïve patients and those previously exposed to BV. Median follow‐up was 20 months. Patients presented a median of two lines of treatment pre‐ASCT, with 51% receiving BV. Twenty‐nine percent of patients had at least two high‐risk factors (refractory disease, complete response [CR] less than 12 months, extranodal disease at relapse), while 16% presented none. At PET‐CT, a Deauville score (DS) of 1–3 was reported in 75% and 78% of pre‐ and post‐ASCT evaluations, respectively. Grade 3–4 adverse events (AEs), mainly peripheral neuropathy, were observed in 16% of patients. Three‐year PFS and overall survival (OS) were 62% and 86%, respectively. According to BV exposure, 3‐year PFS and OS were 54% and 71%, respectively, for naïve and 77% and 96%, respectively, for previously exposed patients. Refractory disease (hazard ratio [HR] 4.46; p  = 0.003) and post‐ASCT DS 4–5 (HR 3.14; p  = 0.005) were the only two factors significantly associated with PFS reduction in multivariable analysis. Post‐ASCT BV maintenance is an effective, safe treatment option for cHL naïve patients and those previously exposed to BV.